Different chemically substituted chitooligosaccharides inhibit beta-secretase activity - Ahmed, A.B.A.; Yoon, N.Y.; Taha, R.M.; Kim, S.K. (2011)
Chitooligosaccharide or COS is a kind of oligosaccharide that is an integral part of the nervous system. COS is synthesized by chemical substitution and derived AE-COS, DEAE-COS and DMAE-COS that are being shown on IC(50) value. AE-COS and DMAE-COS exhibited four fold less inhibition than DEAE-COS. In addition, non-competitive inhibitor was identified via a Dixon plot and the Ki inhibition constant (100 mu g/mL). We declared, chemical substitution of COS is a water soluble human safe BACE-1 inhibitor.